Morpho-physiological response of Acacia auriculiformis as influenced by seawater induced salinity stress - Haque, Md Anamul; Rahman, Md. Mezanur; Nihad, Sheikh Arafat Islam; Amin Howlader, Md. Ruhul; Akand, Md. Mahmudul Hasan (Forest Systems, 2016)
Aim of the study: To evaluate the morpho-physiological changes of Acacia auriculiformis in response to seawater induced salinity stress along with its tolerance limit. Area of study: Bangabandhu Sheikh Mujibur Rahman Agricultural University, Bangladesh. Material and methods: Three saline treatments (4, 8, 12 dS m-1) were applied to six-month aged Acacia auriculiformis seedlings from January 2014 to June 2014 and the tap water was used as control treatment. To observe salinity effects, the following parameters were measured by using various established techniques: plant height and leaf number, plant biomass, shoot and root distribution as well as shoot and root density, water uptake capacity (WUC), water saturation deficit (WSD) and water retention capacity (WRC), exudation rate, and cell membrane stability. Main results: Diluted seawater caused a notable reduction in shoot and root distribution in addition to shoot and root density, though plant height, leaf number and plant biomass were found to be decreased to some extent compared to control plants. Water status of the plant also altered when plants were subjected to salinity stress. Nevertheless, membrane stability revealed good findings towards salinity tolerance. Research highlights: Considering the above facts, despite salinity exerts some negative effects on overall plant performance, interestingly the percent reduction value doesn’t exceed 50% as compared to control plants, and the plants were successful to tolerate salinity stress till the end of the experiment (150 days) through adopting some tolerance mechanisms. Additional key words: Salt stress; halophytes; growth parameters; WUC; exudation rate; membrane stability. Abbreviations used: BSMRAU (Bangabandhu Sheikh Mujibur Rahman Agricultural University); RCBD (randomized complete block design); DATI (days after treatment imposition); RWC (relative water content); WUC (water uptake capacity); WSD (water saturation deficit); WRC (water retention capacity); FW (fresh weight); DW (dry weight); TW (turgid weight); ROS (reactive oxygen species).